The Effect of Relaxation Music Therapy on Reducing Nausea and Vomiting in Pregnant Women with Emesis at UPT Puskesmas Rum Balibunga - Astri Adam; Sulistiyah Sulistiyah (Jurnal Anestesi, 2025)
Nausea and vomiting are common complaints among pregnant women, particularly during the first trimester, and can negatively affect maternal well-being and daily activities. Conventional management often involves pharmacological interventions, which may carry risks or be poorly tolerated. Relaxation music therapy has emerged as a complementary, non-pharmacological approach that may reduce these symptoms by promoting relaxation and psychological comfort. This study aimed to examine the effect of relaxation music therapy on reducing the intensity of nausea and vomiting in pregnant women with emesis gravidarum at UPT Puskesmas Rum Balibunga. A quasi-experimental design with a pretest-posttest control group was employed. Thirty pregnant women were purposively selected and divided into two groups: an intervention group receiving relaxation music therapy for 20–30 minutes, three times a week for two weeks, and a control group receiving standard antenatal care. The severity of nausea and vomiting was assessed using the Pregnancy-Unique Quantification of Emesis and Nausea (PUQE) scale before and after the intervention. Data were analyzed using paired and independent t-tests to compare within-group and between-group differences. The results showed a significant decrease in PUQE scores in the intervention group (mean reduction = 3.7, p = 0.001), while the control group showed a minimal change (mean reduction = 0.3, p = 0.320). Between-group analysis confirmed that relaxation music therapy was more effective than standard care (p = 0.001). In conclusion, relaxation music therapy effectively reduces nausea and vomiting intensity in pregnant women and can be implemented as a safe, low-cost complementary intervention.